ANALISIS PENGARUH PENGETAHUAN TENTANG AKREDITASI TERHADAP BUDAYA KESELAMATAN PASIEN DI RSUD SULTAN SULAIMAN KABUPATEN SERDANG BEDAGAI TAHUN 2019 - Manaluu, Elisabet; Purba, Tetty; Samura, M Dasril (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
The hospital accreditation is a confession to quality of hospital care. It provides a visible commitment to improve the quality of patient care, to ensure a safe environment and to continually work to reduce risks to patients and staffs. Based on patient safety incident report by patient safety hospital committee, in Indonesia was found that there was case report of unexpected incident (14,41%) and nearly injury incident (18,53%) that caused by process or clinical procedur (9,26%), medication (9,26%) and patient harm resulting from falls (5,15%). In Indonesia data about unexpected incident especially nearly injury was rare. It could be influenced by health officer that unknown about the importance of the report. This study aimed to analysis the impact of knowledge about the hospital accreditation to patient safety culture at Sultan Sulaiman General Hospital in Serdang Bedagai Regency in 2019. This study used quantitative method with cross sectional design. Participant of this study was 147 health officer of the hospital. The participants were recruited by using purposive sampling technique. Knowledge about accreditation in this case was representative by Patient Safety Goals that one of standarts in National Standarization of Accreditation of Hospital. The patient safety goals consist of identify patients correctly. Improve effective communication, improve the safety of high alert medications, ensure safe surgery, reduce the risk of health cese-associated infections and reduce the risk of patient harm resulting from falls.Knowledge about patient safety goals has 58,5% moderate level and 41,5% good level. Patient safety culture has 87,1% moderate level and 12,9% good level. All knowledge about patient safety goals has influenced to patient safety culture, but only one that have significant impact to patient safet goals, identify patients correctly. From this result, it can be concluded that higher level of knowledge about identify patients correctly can higher level of patient safety culture.